War on Twitter as a Digital Marketing Communication Strategy: (Electronic Word-of-Mouth Social Network Analysis of Dr. Martens' Products on Twitter) - Khairunnisa Nurul Azizah; Aully, Marfa; Ulhaq, Naufal Dhiya; Salim, Carlos Dewa; Afla, Sandy (Universitas Islam Balitar, 2023)
War on Twitter is a type of social network that is closely related to word-of-mouth marketing communication strategies. The war over #StopLyingDocmart which was popular on 13-16 May 2022 had a good image impact on Dr Martens or Docmart shoe products. This study analyzes social networks and interactions formed through Twitter regarding Docmart products.